Millet biofortification for enhanced iron content: Roadmap for combating hidden hunger - Renu Chaudhary; Charu Sharma; Vijay Kumar; Vishal Rajput; Bindu Naik; Ram Prasad; Shivesh Sharma; Vivek Kumar (Journal of Agriculture and Food Research)
Iron is essential for plant and human health but its deficiency is a global problem, therefore, it is crucial to learn, how to strengthen crop grains with iron to maintain human health. Around, 2 billion people (or 33 % of the world's population) are vulnerable to iron deficiency, which can have serious consequences for adults, infants, and childbearing women. Globally millets constitute an important staple crop, ensuring food and nutritional security, since its grains are a good source of vitamins, essential minerals, and proteins. Diverse approaches, such as conventional, plant breeding, genetic, or the usage of chemical add-ons, have been used to develop fortified millet varieties with augmented iron bioavailability. Use of nano fertilizers is another assuring method for iron biofortification, and exploiting efficient microbes is a promising approach to assist the millet plant in more effectual, successful uptake and translocation of iron. Competent microbes enhance millet growth by mitigating abiotic and biotic stress and enhanced iron uptake by various means. Iron biofortification in millets with plausible approaches to overcome iron malnutrition globally is imperative to feed the world's undernourished people for a reasonable price. We discuss approaches to biofortify millets by encapsulating the prospects to improve bioavailability of iron and also minimizing antinutrients. We conclude that there is an urgent need to biofortify millets with iron using next-generation approaches so that the malnutrition problem can be addressed.